Pembacaan Wahbah Az-Zuhaili Terhadap Term Mubazir Dalam Kitab al-Tafsir al-Munir - Desri Ari Enghariano (Al FAWATIH:Jurnal Kajian Al Quran dan Hadis, 2022)
Islam does not forbid its adherents to enjoy the life of the world. They are allowed and given the freedom to enjoy all the sustenance that Allah has given them. However, the behavior in expressing pleasure should not cross the predetermined line, such as excessive, extravagant and wasteful. But, the reality of the living habits of Indonesian Muslims shows that there are still many who commit wasteful acts, especially in the matter of food. Food that is not spent becomes wasted and wasted, resulting in a very large amount of waste, even up to hundreds of trillions of rupiah per year.Based on the reality of the wasteful behavior of Indonesian Muslims, the author is interested in researching this issue by describing Wahbah Az-Zuhaili's reading of wasteful terms in the book of al-Tafsir al-Munir. This research includes the description of Wahbah Az-Zuhaili regarding the meaning of the word wasteful, the causes of wasteful attitudes, threats to wasteful perpetrators, and solutions to eliminate wasteful attitudes. Thematic method is the choice in completing this research. The results of this research explain that the meaning of redundant is to manage and spend wealth or money not in the right place and not wise in its use. The cause of the emergence of wasteful behavior is not caring about religious teachings and following their lusts. The threat to the wasteful perpetrator is that he will become a brother of Satan and become a disbelief in Allah. The solution to eliminating wasteful nature is to be moderate in the use of wealth, not to distribute wealth in immoral cases, and to distribute wealth to people in need.